Withania somnifera (L.) Dunal ameliorates neurodegeneration and cognitive impairments associated with systemic inflammation - Muskan Gupta; Gurcharan Kaur (BMC, 2019)
Abstract Background Systemic inflammation driven neuroinflammation is an event which correlates with pathogenesis of several neurodegenerative diseases. Therefore, targeting peripheral and central inflammation simultaneously could be a promising approach for the management of these diseases. Nowadays, herbal medicines are emerging as potent therapeutics against various brain pathologies. Therefore, in this contemporary study, the neuroprotective activity of Ashwagandha (Withania somnifera) was elucidated against the inflammation associated neurodegeneration and cognitive impairments induced by systemic LPS administration using in vivo rat model system. Methods To achieve this aim, young adult wistar strain male albino rats were randomized into four groups: (i) Control, (ii) LPS alone, (iii) LPS + ASH-WEX, (iv) ASH-WEX alone. Post regimen, the animals were subjected to Rotarod, Narrow Beam Walking and Novel Object Recognition test to analyze their neuromuscular coordination, working memory and learning functions. The rats were then sacrificed to isolate the brain regions and expression of proteins associated with synaptic plasticity and cell survival was studied using Western blotting and Quantitative real time PCR. Further, neuroprotective potential of ASH-WEX and its active fraction (FIV) against inflammatory neurodegeneration was studied and validated using in vitro model system of microglial conditioned medium-treated neuronal cultures and microglial-neuronal co-cultures. Results Orally administered ASH-WEX significantly suppressed the cognitive and motor-coordination impairments in rats. On the molecular basis, ASH-WEX supplementation also regulated the expression of various proteins involved in synaptic plasticity and neuronal cell survival. Since microglial-neuronal crosstalk is crucial for maintaining CNS homeostasis, the current study was further extended to ascertain whether LPS-mediated microglial activation caused damage to neurons via direct cell to cell contact or through secretion of inflammatory mediators. ASH-WEX and FIV pretreatment was found to restore neurite outgrowth and protect neurons from apoptotic cell death caused by LPS-induced neuroinflammation in both activated microglial conditioned medium-treated neuronal cultures as well as microglial-neuronal co-cultures. Conclusion This extensive study using in vivo and in vitro model systems provides first ever pre-clinical evidence that ASH-WEX can be used as a promising natural therapeutic remedial for the prevention of neurodegeneration and cognitive impairments associated with peripheral inflammation and neuroinflammation.